2015
DOI: 10.1136/gutjnl-2015-310612
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new susceptibility loci for gastric non-cardia adenocarcinoma: pooled results from two Chinese genome-wide association studies

Abstract: Objective Although several genome-wide association studies (GWAS) of non-cardia gastric cancer have been published, more novel association signals could be exploited by combining individual studies together, which will further elucidate the genetic susceptibility of non-cardia gastric cancer. Design We conducted a meta-analysis of two published Chinese GWAS studies (2031 non-cardia gastric cancer cases and 4970 cancer-free controls) and followed by genotyping of additional 3564 cases and 4637 controls in two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 30 publications
2
73
0
Order By: Relevance
“…They are involved in the regulation of gene expression at different levels, affecting multiple cellular processes including cell differentiation, stem cell maintenance, and epithelial–mesenchymal transition 35. Accumulating evidence has strongly suggested that many lncRNAs function as oncogenes and/or tumor suppressors in tumor initiation and development 6. These findings make those lncRNAs potential diagnostic and therapeutic targets in tumor management.…”
Section: Introductionmentioning
confidence: 99%
“…They are involved in the regulation of gene expression at different levels, affecting multiple cellular processes including cell differentiation, stem cell maintenance, and epithelial–mesenchymal transition 35. Accumulating evidence has strongly suggested that many lncRNAs function as oncogenes and/or tumor suppressors in tumor initiation and development 6. These findings make those lncRNAs potential diagnostic and therapeutic targets in tumor management.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer risk SNPs were extracted from the original gastric cancer GWAS studies in GWAS Catalog 5, 6, 7, 8, 9, 10, 27. Only 1 SNP was remained when multiple variants were in linkage disequilibrium (LD, r 2  ≥ .8), and the minor‐allele frequency (MAF) should be greater or equal than .05.…”
Section: Methodsmentioning
confidence: 99%
“…Many genetic variations, most of which are single nucleotide polymorphisms (SNPs), have been detected over the past years by the genome‐wide association studies (GWAS) of gastric cancer 4. These common susceptibility loci included 1q22 ( MUC1 ), 3q13.32 ( ZBTB20 ), 5p13.1 ( PRKAA1 ), 5q14.3 ( lnc‐POLR3G‐4 ), 6p21.1 ( UNC5CL ), 8q24 ( PSCA ), and 10q23 ( PLCE1 ) 5, 6, 7, 8, 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…Analyzed independently of the colonizing H. pylori , these explain a small proportion of estimated heritability of gastric disease [49]. Based on candidate gene studies, host risk factors for gastric cancer include genes encoding cytokines and cytokine receptors like the interleukin-1 (IL-1) family of cytokines (including IL-1β, IL1RN, IL8 and IL-10), TNF-α, stromal remodeling proteins like matrix metalloproteinases, the MUC1 , PRKAA1 and PTGER4 genes and prostate stem cell antigen (PSCA) that acts as a tumor suppressor gene in gastric pathology [5055]. In a seminal study by El Omar, et al, specific pro-inflammatory cytokine genotypes were associated with gastric cancer risk, in the setting of H. pylori infection [56].…”
Section: Human Factors: Germline and Somaticmentioning
confidence: 99%